Schwartz–Jampel syndrome: comprehensive diagnostics and orthopedic treatment - V. M. Kenis; V. N. Komantsev; A. Yu. Dimitrieva; E. V. Melchenko; E. S. Morenko (Нервно-мышечные болезни, 2020)
Schwartz–Jampel syndrome (chondrodystrophic myotonia) is a monogenic genetic disorder, demonstrating unique coincidence of the features of skeletal dysplasia and neuromuscular disease. We present four clinical cases of Schwartz–Jampel syndrome. Principles of diagnostic and results of surgical treatment of the lower limbs deformities are discussed. Importance of this study comprises unique description of rare cases. Surgical treatment for orthopaedic conditions is important and can lead to functional improvement, prevent progression of deformities and enhance daily activity.